ANALISIS KINERJA KEUANGAN KOPERASI PENGUSAHA ANGKUTAN KOTA (KOPATA) PURWOKERTO PERIODE 2007 – 2011 - Banani, Ade (Performance, 2014)
This research was conducted at Koperasi Pengusaha Angkutan Kota (KOPATA) Purwokerto during 2007 to 2011. The objectives of this research were to know the financial performance of (KOPATA) Purwokerto during 2007 to 2011 and to know the tendency of financial performance of KOPATA Purwokerto during 2007 to 2011.The methods used in this research were financial performance analysis based on the decree of Minister of Cooperative, Small and Medium Business No.14/M.KUKM/XII/2009 consisting seven aspects such as Capital Structure, Asset Quality, Management, Efficiency, Liquidity, Independence and Growth, the Cooperative Identity and Trend Analysis.The result of this research showed that the average of financial performance scores of KOPATA Purwokerto during 2007 to 2011 was 58,10 located under the value 60 ≤ x ≤ 100, so it can be classified as “Unhealthy”. Then, the result was based on trend analysis calculation showed that its equation had negative slope (-0,125). It meant that the trend of financial performance tend to decrease or projected to fall.The implication of conclusion above was KOPATA Purwokerto should maximize its idle assets to optimize its profit for example, by expanding new business such as rental facilities and providing spar-parts needed by members. KOPATA Purwokerto should pay attention the application of 5C’s analysis such as Character, Capacity, Capital, Collateral and Condition of Economic to minimize the risk and troubled loans/non performing loan